Cretaceous beetles from Jinju Formation: Trachypachidae (Coleoptera: Adephaga) - Lee, Soo Bin; Nam, Gi Soo; Park, Jong Kyun (Zootaxa, 2024)
Here we describe two new species, Psacodromeus recta sp. nov. and Necronectulus lazarus sp. nov., that belong to the family Trachypachidae. Only one species of the genus Psacodromeus, P. minor, was reported from the Gurvaneren Formation in Mongolia, which is estimated as Early Cretaceous. Other species of the genus Psacodromeus, including P. crassus, P. gutta, P. ovalis, and P. rugosus, were reported from the Karabastau Formation in Kazakhstan, which is dated to the Late Jurassic. Necronectulus avus, which is the only species of the genus Necronectulus, was reported from the Tologoi Formation in Kazakhstan, which is dated to the Late Triassic. Therefore, our study has expanded the fossil record of the genera Psacodromeus and Necronectulus from the Early Cretaceous.